1995
DOI: 10.1007/bf02431931
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of 2,4,6-trinitrotoluene byMycobacterium vaccae

Abstract: Mycobacterium vaccae strain JOB-5 cometabolized 2,4,6-trinitrotoluene (TNT) in the presence of propane as a carbon and energy source. Two novel oxidized metabolites, as well as several known reduced products, were generated during catabolism of TNT by M. vaccae. During the cometabolic process, there was transient production of a brown chromophore. This compound was identified as 4-amino-2,6-dinitrobenzoic acid. When M. vaccae was incubated with [14C]TNT and propane, 50% of the added radiolabel was incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These residues could originate from reactions of partially oxidized methyl groups with soil organic matter. The formation of such nitrobenzoic acids has been described earlier by several authors during incubation of TNT with bacterial cultures (28) and in contaminated soils (29)(30)(31)(32)(33)(34). As intermediates of the oxidation of the methyl group highly reactive aldehyde groups could be formed and bind covalently to soil organic matter.…”
Section: Resultsmentioning
confidence: 75%
“…These residues could originate from reactions of partially oxidized methyl groups with soil organic matter. The formation of such nitrobenzoic acids has been described earlier by several authors during incubation of TNT with bacterial cultures (28) and in contaminated soils (29)(30)(31)(32)(33)(34). As intermediates of the oxidation of the methyl group highly reactive aldehyde groups could be formed and bind covalently to soil organic matter.…”
Section: Resultsmentioning
confidence: 75%
“…Soil columns with radiolabeled immobilized contaminants are subjected to different time lapse leaching conditions in order to mimic natural catabolic processes in soil. Taking into account that hydroxylaminodinitrotoluenes are often described as initial TNT metabolites in various microbial systems under anaerobic or aerobic conditions (4, 5, [33][34][35][36][37][38][39], irreversible binding of these compounds to soil components especially to humic material may play a major role in TNT bioremediation processes. In some cases the condensation of the hydroxylaminodinitrotoluenes with related nitroso compounds also led to an accumulation of azoxy compounds (40) which, however, were not observed at the end of the present bioremediation.…”
Section: Ecotoxicological Evaluation Of the Bioremediated Soilmentioning
confidence: 99%
“…Indeed, there is strong evidence supporting TNT-degrading abilities of fungi [17][18][19][20] and plants [21][22][23]. Furthermore, previous studies showed that several bacteria, such as Pseudomonas [1], Bacillus [24], Enterobacter [25], and Rhodococcus [26], were capable of degrading TNT. The main products of microbial TNT degradation and the extent of such reactions were influenced by the types of microorganisms and culture conditions used [15].…”
Section: Introductionmentioning
confidence: 99%